GURU SUŚRUSA DALAM TEKS ĀDIPARWA - Ida Bagus Subrahmaniam Saitya (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Catur guru means four teachers or people who are knowledgeable and provide enlightenment and are able to direct others. In Hinduism, guru is a symbol for a sacred place that contains knowledge (vidya) and also the divisor of knowledge. Catur guru consist of guru rupaka, recitation teacher, local teacher, and self-help teacher. In the teachings of Pañca Nyama Brata there is the teaching of the guru suśrusa. Guru suśrusa means listening to or paying attention to the teachings and advice of the guru. In the Ādiparwa text it is told when the Sang Aruṇika carried out his duty to guard the rice field ordered by his teacher Bhagawān Dhomya. Another student, Sang Utamanyu, was instructed to herd cattle, in carrying out his duties he was very hungry and thirsty so he begged for people, but that was prohibited by Bhagawān Dhomya. Furthermore, Sang Utamanyu drank the rest of cow's milk from the herded calf was also forbidden by his teacher so he drank the sap of waduri leaves which caused the Utamanyu to become blind. The act is a manifestation of the teachings of teachers who are sincere to a teacher. The teachings of the guru suśrusa were also demonstrated by Sang Weda to the teacher. He was ordered to cook and serve various dishes and the order of the Bhagawān Dhomya was carried out as well as possible. The teaching of the guru suśrusa is closely related to the devotional teacher. Bhakti is not only for God, bhakti teachings are also applied to parents. Bhīṣma with his devotion to his father Śantanu was willing to brāhmacari for the rest of his life and did not become king in Hāstina so that his father could marry Gandhawati. The form of devotional service to parents was also demonstrated by the Garuḍa to free his mother Winatā from the enslavement carried out by Kadrū along with her children.